ANALISA PENERAPAN ANIMASI INTERAKTIF SEBAGAI MEDIA PEMBELAJARAN IPA PADA SMAN 7 BEKASI - Indarti Indarti (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2014)
The application of multimedia is used to process the teaching to be made, interactive easy to digest by all the students. By learning based multimedia that is tools of knowledge management the process of development knowledge not only happened indoors class course, where teachers give the subject matter indirect but with equipment supply computers, application program multimedia and tissue, the students can actively be involved in the learning process independently to visit the library and other facility equipped facilities to learn to use multimedia to improve performance students in a school. This research uses the theory of acceptance and use of technology (UTAUT) with data analysis using structural equation modeling (SEM) of the software analysis of moment structure (AMOS) version 7.0. Variable used in this approach is latent exogen variable as independent variable ( x or ability to use computers and endogenous variable latent as the dependent variable (y): performance of expectancy (pe), effort expectancy (ee), social influence (si), facilitating precedent (FC), attitude toward technology (at), symbolic adoption (sa),